Menelaah Desekuritisasi : Analisis Praksis Hansenian Desekuritisasi Melalui Transformasi Kebijakan Kanabis Amerika Serikat - Nurridho Aryawan (Sociale : Journal of Social and Political Sciences, 2025)
Although the concepts of securitization and desecuritization in the realm of international security studies emerged simultaneously and are inseparable from one another, the concept of desecuritization has not undergone as comprehensive development as the concept of securitization. The development of desecuritization is conceptually fragmented and often contradictory to one another. Utilizing a case study of the transformation of United States' cannabis policy patterns both home and abroad alongside Lene Hansen's concept of desecuritization, this paper attempts to illustrate how Hansenian desecuritization theory enables the simultaneous use of different desecuritization concepts in analyzing a single case study. This paper identifies three type of desecuritization that leads to the transformation of United States cannabis policy, including: i) the type of desecuritization change through stabilization, where the dynamics of the issue remain stable for a considerable period, thus removing the cannabis issue from the realm of security, ii) replacement type, in which the emergence of new threats in renders the old issue in security discourse no longer relevant, and iii) rearticulation type, where efforts are made by actors to change old cannabis policy patterns. Moreover, this paper finds that although one desecuritization process does not always occur simultaneously with another desecuritization process, each of them still influences the process of an issue transitioning from a security issue to a normal-political issue